Impact of electroanatomical mapping-guided lead implantation on procedural outcome of His bundle pacing. Issue 3 (30th November 2020) - Richter, Sergio; Ebert, Micaela; Bertagnolli, Livio; Gebauer, Roman; Lucas, Johannes; Scheller, Dominik; Paetsch, Ingo; Hindricks, Gerhard; Döring, Michael
Abstract: Aims: Conventional His bundle pacing (HBP) can be technically challenging and fluoroscopy-intense, particularly in patients with His-Purkinje conduction disease (HPCD). Three-dimensional electroanatomical mapping (EAM) facilitates non-fluoroscopic lead navigation and HB electrogram mapping. We sought to assess the procedural outcome of routine EAM-guided HBP compared with conventional HBP in a real-world population and evaluate the feasibility and safety of EAM-guided HBP in patients with HPCD. Methods and results : We included 58 consecutive patients (72 ± 13 years; 71% male) who underwent an attempt to conventional (EAM− group; n = 29) or EAM-guided (EAM+ group; n = 29) HBP between June 2019 and April 2020. The centre's learning curve was initially determined ( n = 40 cases) to define the conventional control group and minimize outcome bias favouring EAM-guided HBP. His bundle pacing was successful in 26 patients (90%) in the EAM+ and 27 patients (93%) in the EAM− group ( P = 0.64). The procedure time was 90 (73–135) and 110 (70–130) min, respectively ( P = 0.89). The total fluoroscopy time [0.7 (0.5–1.4) vs. 3.3 (1.4–6.5) min; P < 0.001] and fluoroscopy dose [21.9 (9.1–47.7) vs. 78.6 (27.2–144.9) cGycm 2 ; P = 0.001] were significantly lower in the EAM+ than EAM− group. There were no significant differences between groups in His capture threshold (1.2 ± 0.6 vs. 1.4 ± 1.0 V/1.0 ms; P = 0.33) and paced QRS duration (113 ± 15 vs. 113 ± 17 ms; P = 0.89). In patients with HPCD, paced QRS duration was similar in both groups (121 ± 15 vs. 123 ± 12 ms; P = 0.77). The bundle branch-block recruitment threshold tended to be lower in the EAM+ than EAM− group (1.3 ± 0.7 vs. 1.8 ± 1.2 V/1.0 ms; P = 0.31). No immediate procedure-related complications occurred. One patient (2%) experienced lead dislodgement during 4-week follow-up. Conclusion : Implementation of routine EAM-guided HBP lead implantation is feasible and safe in a real-world cohort of patients with and without HPCD and results in a tremendous reduction in radiation exposure without prolonging procedure time or increasing procedure-related complications.